Genetic risk and plasma biomarkers of dementia with Lewy bodies in a Chinese population - Xiaoli Hao; Xuewen Xiao; Ling Weng; Zhuojie Lin; Qian Xu; Juan Du; Qijie Yang; Yuan Zhu; Yiliang Liu; Tianyan Xu; Yafang Zhou; Xinxin Liao; et al. (npj Parkinson's Disease)
Abstract Genetic investigations and associations with plasma biomarkers of dementia with Lewy bodies (DLB) in East Asian populations are lacking. The aim of our study is to identify candidate pathogenic variants and assess the diagnostic performance of plasma biomarkers among DLB patients in the Chinese population. This cohort included 151 DLB patients and 2010 controls, all of whom underwent whole genome sequencing. Plasma glial fibrillary acidic protein (GFAP), α-synuclein(αSyn), neurofilament light (NfL), and phosphorylated tau 217 (p-tau217) were detected in a subgroup. As a result, the APOE ε4 allele significantly increased DLB risk (p = 1.84E-11), while rare missense variants of USP13 gene were first found to be suggestively associated with DLB risk (p = 1.31E-5). Higher levels of plasma GFAP, αSyn, NfL, and p-tau217 were detected in DLB patients compared to controls (p < 0.001), which combined with polygenic risk scores (PRS) achieving an AUC of 0.927 for DLB diagnosis. Besides, significant correlations were observed between PRS of DLB and age at onset, the cumulative incidence rate, as well as plasma GFAP levels. In conclusion, this is the first study to simultaneously investigate the genetics and plasma biomarkers of DLB, highlighting the discriminative ability for DLB using PRS and plasma biomarker assay.